ANAESTHETIC PHARMACODYNAMICS IN HORMONE-RECEPTOR POSITIVE VS. TRIPLE-NEGATIVE BREAST CARCINOMA PATIENTS (The Research of Medical Science Review, 2025)
Pharmacodynamical effects of anesthetics may differ markedly among individual patients, which may be influenced by underlying biology of the disease. Breast cancer is divided into subtypes according to hormone receptor status, as hormone receptor-positive (HR+) and triple-negative (TNBC) breast cancer, which may present different clinical features and systemic inflammatory signatures, possibly having impact in anesthetic strategy and postoperative recovery. We prospectively compared anesthetic responses in HR+ and TNBC patients undergoing breast cancer surgery at a single tertiary care Centre (JPMC). This was a prospective observational study at Jinnah Postgraduate Medical Centre (JPMC), Karachi on 120 female patients affected by HR+ (n=60) or TNBC (n=60) subtypes who underwent breast surgery. Demographic and clinical information was collected. Intraoperative anesthetic use (sevoflurane, propofol, fentanyl, rocuronium) and hemodynamic (mean arterial pressure, MAP; heart rate, HR; hypotension) variables and variability were recorded. Postoperative pain (VAS at 2 h, 6 h, and 24 h), morphine consumption and postoperative cognitive dysfunction (POCD) with MMSE scores were measured. T-tests and chi-square analyses were performed to compare groups; correlation matrices were developed. Sevoflurane usage (1.75 ± 0.35 vs 1.32 ± 0.28 MAC-hours, p=0.0003), propofol infusion rates (4.8 ± 1.1 vs 4.1 ± 0.9 mg/kg/h, p=0.012), and fentanyl requirement (215 ± 53 vs 185 ± 45 μg, p=0.018) were all significantly higher in TNBC patients. The TNBC group had hemodynamic instability, as shown by more MAP variation >20% (23.3% vs 8.3%, p=0.004) and vasopressor drugs need (31.6% vs 11.7%, p=0.002). TNBC patients reported greater VAS scores at all time points (5.1 vs 3.6 at 2 hours, p<0.001) and with higher morphine consumption (7.6 ± 2.0 vs 5.2 ± 1.4 mg, p<0.001). POCD was more common (28.9% vs 11.1%, p=0.006) and severe in TNBC patients. Strong positive correlations were observed between tumor subtype and sevoflurane usage (r=0.41), VAS score (r=0.48) and POCD score (r=0.38). The results indicate TNBC patients at Jinnah Postgraduate Medical Centre (JPMC), Karachi have specific anesthetic pharmacodynamics profiles manifested by higher drug needs, greater hemodynamic fluctuation, more intense pain experience, and more pronounced neurocognitive dissonance. These findings support a personalized, subtype-specific paradigm for anesthetic stratagem in breast cancer operation.